Chapter 11 Popularizing "American-ness" - Blu Wakpa, Tria (Taylor & Francis, 2024)
Chapter 11, "Popularizing 'Americanness,'" analyzes how The Halluci Nation's 2016 award-winning music video, "Stadium Pow Wow," challenges dominant pop culture discourses in powerful ways. The Halluci Nation are a DJ collective-composed of First Nations artists-who have created an innovative musical style. To date, "Stadium Pow Wow" has garnered over 7.9 million views on YouTube. Contemporary "American" mainstream-that is, settler colonial-pop culture discourses frequently exclude Native Americans and their practices and/or relegate them to a historic past. Such structural exclusion of Indigenous peoples produces detrimental, material consequences. This chapter focuses on what insights can be gleaned from considering the connectedness of the disparate movement modalities depicted in the music video, which include Grass Dance, Hoop Dance, skateboarding, protest, boxing, and play. Interviews with three practitioners in the film who are prominently featured-Adrian Primeaux, Joe Buffalo, and Kenzie Wilson-inform this chapter in important ways. This chapter argues that "Stadium Pow Wow" expands dominant pop culture discourses by (1) making visible contemporary Native people, practitioners, and lands, challenging patriarchal gender norms and (2) articulating human-to-human and more-than-human linkages in the past and present to bring an Indigenous future into being.